The Strategic Role of Higher Education in the Sustainable Development of the Caribbean - Bynoe Paulette (Revista Educación Superior y Sociedad (ESS), 2019)
Education as a process allows human beings and societies to reach their fullest potential, while improving their capacity to address environment and development issues (Chapter 36, Agenda 21); by reasoning therefore, higher education should be pivotal to the achievement of sustainable development of the Caribbean Region. Currently, however, there are many issues that must be addressed by the Caribbean Community governments and higher education institutions prior to the realization of such laudable goals. The purpose of this Case Study is to demystify the typologies of Education for Sustainable Development, examine the current sustainable development practice of the University of Guyana in respect of its academic programmes and curricula, institutional practice regarding resource consumption (including water, energy, and paper), research agenda, and services (including policy advice) to the wider society. To this end, the research strategy entailed desk review of documents, key informants’ semi-structured interviews, and a survey of lecturers. The results highlight good practices can be replicated or scaled up, as well as gaps and opportunities for improvement.